Peran analisis SWOT pada manajemen strategi perbankan syariah - Devi, Haura Awalin Nurista (Maliki Interdisciplinary Journal, 2025)
This article discusses the role of SWOT analysis in the strategic management of Islamic banking. By using the SWOT method (Strengths, Weaknesses, Opportunities, Threats), Islamic banks can identify internal strengths, such as compliance with sharia principles, and address weaknesses, such as technological limitations. Additionally, opportunities arising from increased public awareness of sharia-compliant financial products and regulatory support can be optimized to expand the market. However, Islamic banks also face threats from stiff competition with conventional banks and global economic volatility. The article concludes that SWOT analysis is crucial for formulating appropriate business strategies, ensuring operational sustainability, and enhancing the competitiveness of Islamic banking in an increasingly competitive global market. Islamic banks are advised to invest in technology, develop innovative products, and improve human resource competencies to adapt to the ever-evolving financial industry dynamics.